2019
DOI: 10.1371/journal.pone.0220660
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age on stage-specific mortality in patients with gastric cancer: A long-term prospective cohort study

Abstract: Controversies exist regarding the impact of age on gastric cancer-related mortality according to cancer stage. In our prospective cohort study, we evaluated the impact of age on stage-specific mortality in patients with gastric cancer. Between 2002 and 2006, patients with newly diagnosed gastric cancer were recruited from two university-affiliated hospitals in Korea. Follow-up data were updated regularly based on medical records and telephone surveys. Patients were classified into four subgroups according to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Recent research suggested that the impact of age as an independent risk factor on gastric cancer may differ depending on the cancer stage [ 62 ]. Although the finding of age as an independent risk factor in this study had a certain particular value, large-scale clinical data is urgently needed to verify and thus to direct the establishment of a clinical treating scheme.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research suggested that the impact of age as an independent risk factor on gastric cancer may differ depending on the cancer stage [ 62 ]. Although the finding of age as an independent risk factor in this study had a certain particular value, large-scale clinical data is urgently needed to verify and thus to direct the establishment of a clinical treating scheme.…”
Section: Discussionmentioning
confidence: 99%
“…Although considered as an independent risk factor for GC-related mortality, the impact of age may differ depending on the stage of cancer. 27 In the Dutch CRITICS trial, out of 788 randomized patients, 22% were older (≥70 years) adults with resectable GC who received preoperative chemotherapy (3 cycles of EOX/ECX), followed by surgery, and postoperative radio and/or chemotherapy. Although they frequently (77%) experienced severe toxicity, and thus received lower relative dose intensities during preoperative chemotherapy, equal proportion (80%) of older patients underwent curative surgery as compared to younger ones.…”
Section: Elderlymentioning
confidence: 99%
“…Patients with stage IV disease, who underwent palliative treatment, and who received support care alone were included. Margins and lymphadenectomy performed and not reported (19) . In our cohort, aging significantly increased complications and shortened OS.…”
Section: Discussionmentioning
confidence: 99%